Organosilane surfactant-assisted synthesis of mesoporous SSZ-39 zeolite with enhanced catalytic performance in the methanol-to-olefins reaction - Xu, Hao; Lei, Chi; Wu, Qinming; Zhu, Qiuyan; Meng, Xiangju; Dai, Daniel; Maurer, Stefan; Parvulescu, Andrei-Nicolae; Müller, Ulrich; Xiao, Fengshou (Frontiers of chemical science and engineering, 2020)
SSZ-39 zeolite with AEI framework structure is a good catalyst candidate for the methanol-to-olefins (MTO) reaction. However, the diffusion limitation and coke formation often results in fast deactivation of the SSZ-39 zeolite catalyst. One solution for this challenge is to introduce mesoporosity in the SSZ-39 zeolite. Herein, we report the synthesis of mesoporous SSZ-39 zeolite using an organosilane surfactant, N , N -dimethyl- N -(3-(trimethoxysilyl)propyl)octan-1-aminium chloride, as a mesopore template and N , N -dimethyl- cis -2,6-dimethylpiperidinium as a micropore template. The obtained zeolites were characterized by X-ray diffraction, N 2 sorption, scanning electron microscopy, temperature programmed desorption of ammonia, and magic angle spinning nuclear magnetic resonance of 27 Al. The results show that the mesoporous SSZ-39 zeolite has high crystallinity, meso/microporosity, high surface area, cuboid morphology, and abundant acidic sites. More importantly, this mesoporous SSZ-39 zeolite exhibits enhanced catalyst lifetime in the MTO reaction due to the presence of mesoporosity for fast mass transfer, compared with a conventional SSZ-39 zeolite without mesoporosity.